Knowledge, practices and attitudes associated with clinical signs related to cystic echinococcosis in secondary school students and teachers in the high Andean district of Huancarama, Peru - Valderrama P., Aldo (2024)
The aim of the study was to determine the knowledge, practices and attitudes associated with clinical signs related to cystic echinococcosis in students and teachers of secondary education in the district of Huancarama, department of Apurímac, Peru, an endemic area of this parasitosis. The research was at basic level, with an analytical and cross-sectional design. The corresponding informed consent and assent were obtained. The clinical signs, knowledge, practices and attitudes regarding cystic echinococcosis, as well as the nutritional status and haemoglobin values of the participants were determined. The most frequent clinical signs of cystic echinococcosis were weakness (34.9%), disorientation (34.6%), drowsiness (32.7%) and abdominal pain (31.4%). Male sex was a protective factor against abdominal pain, nausea, vomiting, cough, chest pain, dyspnoea, anorexia, weight loss, malaise and drowsiness. Living in a rural area was also a protective factor for abdominal pain, nausea, cough, chest pain, dyspnoea, anorexia, weight loss, weakness, malaise, ascites, disorientation, and drowsiness. However, drinking unboiled water was a risk factor for nausea, anorexia, weight loss, malaise, and disorientation. Slaughtering livestock at home was also associated with cough, disorientation and drowsiness.